HUBUNGAN PENGETAHUAN TENTANG KESEHATAN GIGI DAN MULUT DENGAN PERILAKU MENGGOSOK GIGI PADA ANAK USIA SEKOLAH SDN CIPINANG BESAR UTARA 10 PAGI JAKARTA TIMUR - kusdiah eny (Afiat, 2023)
Dental and oral health is a support for achieving optimal body health. How to brush your teeth properly is very important to teach children because it greatly affects the level of dental hygiene. The purpose of this study was to see the relationship between school-age children's knowledge of oral and dental health and tooth brushing behavior in Grades 1A and 1B of SDN Cipinang Besar Utara 10 Pagi. This study design uses descriptive correlative with a cross sectional approach. The sampling technique is total sampling. The sample in this study were 66 students. The results of this study showed that 46 students (69.7%) lacked knowledge and 45 students (68.2%) had bad tooth brushing behavior. Statistical test results using the Chi Square test with a value of ρ = 0.003 when compared with α = 0.05, then ρ value <0.05. This shows that Ha is accepted. It can be concluded that in this study there is a relationship between dental and oral health knowledge in school children and brushing behavior in Class 1A and 1B SDN Cipinang Besar Utara 10 Pagi. Suggestions for schools are that it is hoped that they can work together with the local health center to provide health education on tooth brushing behavior in an effort to improve dental and oral hygiene.